COMPUTER AIDED DESIGN OF 1, 2, 3, 4,-TETRAHYDROPYRIMIDINE DERIVATIVES CONTAINING CARBAMATES AND CARBAMIDES: AS SELECTIVE CALCIUM CHANNEL BLOCKERS - SANDIP S. KSHIRSAGAR; P. SHANMUGASUNDARAM (International Journal of Pharma and Bio Sciences, 2014)
The curtius rearrangement of Ethyl - 1 - (2 – azido – 2 - oxoethyl) – 6 – methyl – 2 – oxo – 4 – (3 – substituted) - 1, 2, 3, 4 – tetrahydropyrimidine -5 – carboxylate prepared from the readily accessible 4 - (1 – substituted) – 5 - ethoxy carbonyl – 6 - methyl] - 3, 4 –dihydropyrimidine – 2 (1H) – one was investigated in presence of ethanol, substituted phenols and substituted amines. The resulting carbamates and carbamides were has been made to correlate the calcium channel blocking activity to the physicochemical descriptors through QSAR studies. kNN- MFA and other advanced methods of analysis were opted for a set of twelve derivatives to figure out the correlationship between steric and electrostatic descriptors. In 3D-QSAR, statistically significant model 2 was obtained using simulated annealing algorithm, with the corresponding q2 and pred_r2 values 0.5141and 0.1109 respectively, showing internal and external predictivities 51% and 11 % respectively. The ten descriptors which contributed significantly to the model were E_945, S_764, S_897, E_774, E_898, S_973, E_383, E_319, S_832, E_546. The models were found to show good statistical and predictive significance which can further be used for guiding ligand modification for the development of potential calcium channel blocking agents.